Some results on cascade discrete-time systems (Discrete Dynamics in Nature and Society)
We present sufficient conditions for global asymptotic stability of cascade discrete-time systems. Considering failure of the global asymptotic stability in some cascade systems, we give an estimate of the region of attraction of the systems.